Dissolved methane recovery from anaerobic effluents using hollow fibre membrane contactors - Cookney, Joanna; McLeod, Andrew J.; Mathioudakis, Vasileios; Ncube, Philani; Soares, Ana; Jefferson, Bruce; McAdam, Ewan J. (Elsevier, 2015)
Hollow fibre membrane contactor (HFMC) systems have been studied for the desorption of dissolved methane from both analogue and real anaerobic effluents to ascertain process boundary conditions for separation. When using analogue effluents to establish baseline conditions, up to 98.9% methane removal was demonstrated. Elevated organic concentrations have been previously shown to promote micropore wetting. Consequently, for anaerobic effluent from an upflow anaerobic sludge blanket reactor, which was characterised by a high organic concentration, a nonporous HFMC was selected. Interestingly, mass transfer data from real effluent exceeded that produced with the analogue effluent and was ostensibly due to methane supersaturation of the anaerobic effluent which increased the concentration gradient yielding enhanced mass transfer. However, at high liquid velocities a palpable decline in removal efficiency was noted for the nonporous HFMC which was ascribed to the low permeability of the nonporous polymer provoking membrane controlled mass transfer. For anaerobic effluent from an anaerobic membrane bioreactor (MBR), a microporous HFMC was used as the permeate comprised only a low organic solute concentration. Mass transfer data compared similarly to that of an analogue which suggests that the low organic concentration in anaerobic MBR permeate does not promote pore wetting in microporous HFMC. Importantly, scale-up modelling of the mass transfer data evidenced that whilst dissolved methane is in dilute form, the revenue generated from the recovered methane is sufficient to offset operational and investment costs of a single stage recovery process, however, the economic return is diminished if discharge is to a closed conduit as this requires a multi-stage array to achieve the required dissolved methane consent of 0.14 mg l−1.
Keywords: Stripping; Degassing; Desorption; Fracking; Fugitive emission; Greenhouse gas